SYSTEMATIC LITERATURE REVIEW: FOSTERING ORGANIZATIONAL TRANSFORMATION IN HIGHER EDUCATION TOWARDS SUSTAINABLE DEVELOPMENT - Shoimah, Siti; Ayu, Intan (Fakultas Ekonomi, 2024)
This systematic literature review explores the role of organizational transformation within higher education institutions as a pivotal component in advancing sustainable development. As higher education institutions are uniquely positioned to drive societal and environmental progress, their transformation towards sustainability is crucial. This review synthesizes recent research on how these institutions can integrate sustainability principles into their operations, curricula, and governance structures. By analyzing 16 empirical studies from 2020 to 2024, this review identifies key trends, challenges, and best practices associated with organizational transformation in higher education. Findings reveal that successful transformation involves a comprehensive approach encompassing curriculum development, research initiatives, facilities management, community outreach, and governance practices. The review highlights the need for a systemic shift that integrates sustainability into all facets of university operations to achieve long-term impact. It provides insights into how higher education institutions can effectively contribute to the Sustainable Development Goals (SDGs) by adopting transformative practices and fostering a culture of sustainability. The study concludes with recommendations for future research and practical implications for higher education leaders aiming to enhance their sustainability efforts.